Photo recipes live. behind the scenes : your guide to the most popular lighting techniques - Kelby, Scott (Kelbytraining.com, 2009)
"Scott Kelby, author of the best-selling The Digital Photography Book, brings to life his "Photo Recipes" chapter--not just from this book, but from his smash best-selling follow-ups, volumes 2 and 3. If you've ever wondered how the pros use natural light, studio light, and even direct daylight to get those amazing shots, you'll see it all here, live, as it happens. Most of the shoot takes place in an amazing New York City loft photo studio as Scott re-creates the looks he describes in the book, along with some bonus lighting set-ups that aren't in the book, to create a very special learning experience you won't find anywhere else"--Resource description page.